PENGARUH PENGGUNAAN MASKER LIDAH BUAYA TERHADAP PERAWATAN KULIT WAJAH KERING - HANZOLA, GITA FADHILA; Rahmiati, Rahmiati; Astuti, Murni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aimed to analyze the effect of the use of aloe vera mask for dry facial skin care is done once in 2 weeks with assessment indicators at the level of skin moisture, and the brightness of the skin. This study uses a pre experiment with designs (one group pretest - porstest design). The number of samples are 5 people taken through purposive sampling technique to sample selection tailored to specific criteria. Assessment conducted by panelists who are 5 people using observation sheet. The data analysis technique used is the analysis of paired samples t test to compare the treatment of pretest and posttest, before the t test to test for normality and homogeneity. The results showed that the effect of the use of Aloe Vera mask to dry facial skin care skin moisture indicator shows the highest scores in the fourth and fifth treatment with an average score of 4.0 category Ultra Moist. The proposed hypothesis is accepted at the 5% significance level for the price of t> t table (8.552> 2.776) and (8.552> 4.604) at a significance level of 0.01 (1%). Effect of Aloe Vera mask for dry facial skin care in skin brightness indicator shows the highest scores in the fifth treatment with an average score of 3.0 category Bright. The proposed hypothesis is accepted at significance level of 95% due to the price of the t> t table (5.262> 2.776) and (5.262> 4.604) at the significance level of 0.1 (1%). Based on the research results prove mask Aloe Vera gel can moisturize and brighten the skin dry.Keywords: Humidity facial skin, facial skin brightness